Znaczenie odstraszania strategicznego dla bezpieczeństwa międzynarodowego: Importance of strategic deterrence for international security - Banasik, Mirosław (Przegląd Wschodnioeuropejski, 2021)
The aim of the article was to clarify the essence of the strategic deterrence and to characterize the deterrent mechanisms used to shape international security. The article explains the nature of the deterrent and mechanisms to guarantee international security. It presents the genesis of deterrence and characterizes its evolution. It also indicates the need for changes in the theory and practice of deterrence. As a result of the studies, it has been established that, nowadays, thanks to the complementary use of hard and soft power, strategic deterrence has a multi-faceted character and its importance for international relations is increasing. It is closely linked to diplomacy and constitutes a mechanism, by means of which the foreign political interests of states are realized and the international security order is shaped.